Synthesis and Preclinical Evaluation of Urea-Based Prostate-Specific Membrane Antigen-Targeted Conjugates Labeled with 177 Lu - Machulkin, Aleksei E.; Petrov, Stanislav A.; Bodenko, Vitalina; Larkina, Mariia S.; Plotnikov, Evgenii; Yuldasheva, Feruza; Tretyakova, Maria; Bezverkhniaia, Ekaterina; Zyk, Nikolay Yu; Stasyuk, Elena; Zelchan, Roman; Majouga, Alexander G.; et al. (ACS pharmacology & translational science, 2024)
Lu-labeled small-molecule prostate-specific membrane antigen (PSMA) targeted tracers are therapeutic agents for metastatic castration-resistant prostate cancer. Optimizing molecular design holds the potential to further enhance the pharmacokinetic properties of PSMA-targeted agents while preserving their potent therapeutic effects. In this study, six novel -[ -[( )-1,3-dicarboxypropyl]carbamoyl]-( )-l-lysine (DCL) urea-based PSMA ligand 2,2',2″,2‴-(1,4,7,10-tetraazacyclododecane-1,4,7,10-tetrayl)tetraacetic acid conjugates were synthesized. These conjugates feature polypeptide linkers containing the Phe-Phe peptide sequence and an aromatic fragment at the ε-NH-Lys group of the DCL fragment. The synthesis yielded products with satisfactory yields ranging from 60% to 72%, paving the way for their preclinical evaluation. The labeling of the new variants of urea-based PSMA inhibitors provided a radiochemical yield of over 95%. The Lu-labeled conjugates demonstrated specific and moderate affinity binding to PSMA-expressing human cancer cells PC3-pip in vitro and specific accumulation in PSMA-expressing xenografts in vivo. Based on the results, both the lipophilicity and the type of substituent in the linker significantly influence the binding properties of the PSMA inhibitor and its biodistribution profile. Specifically, the studied variants containing a bromine substituent or a hydroxyl group introduced into the aromatic fragment of the phenylalanyl residue in DCL exhibit higher affinities to PSMA compared to variants with only a chlorine-substituted aromatic fragment or variants without any substituents. The [ Lu]Lu- with the bromine substituent was characterized by the highest activity accumulation in blood, salivary glands, muscle, bone, and gastrointestinal tract and had inasmuch as an unfavorable pharmacokinetic profile. The negative charge of the carboxyl group in the phenyl moiety of the [ Lu]Lu- variant has demonstrated a positive effect on reducing the retention of activity in the liver and the kidneys (the ratio of tumor to kidneys was 1.3-fold). Low accumulation in normal tissues in vivo indicates that this novel PSMA-targeting inhibitor is a promising radioligand.